All Days 2010
DOI: 10.2118/137728-ms
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CO2 Flooding Potential for Bakken Formation, Saskatchewan

Abstract: The Bakken is an extremely tight formation, with the oil contained mostly in siltstone and sandstone reservoirs with low porosity and permeability. In Saskatchewan alone, there could be an estimated 25 to 100 billion barrels of Bakken oil in place. At present, the combination of horizontal well drilling and the new multi-stage fracturing and completion technologies has been the key to economically unlocking the vast reserves of the Bakken formation. The primary recovery factor, however, remains rather low due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Hoffman [19] studied the injection of hydrocarbon gases in the continuous injection mode, and concluded that ''miscible hydrocarbon injection performs as well as miscible CO 2 .'' Meanwhile, Wang et al [20] found that CO 2 -enriched produced gas (60-40 mol% CO 2 -CH 4 ) and CO 2 -enriched flue gas (60-40 mol% CO 2 -N 2 ) display ''high oil recovery performance'' and would be efficient choices for gas flooding projects in the Bakken. Two cases were run, each consisting of a 4-cycle Huff-and-Puff treatment.…”
Section: Composition Of the Injection Gasmentioning
confidence: 99%
“…Hoffman [19] studied the injection of hydrocarbon gases in the continuous injection mode, and concluded that ''miscible hydrocarbon injection performs as well as miscible CO 2 .'' Meanwhile, Wang et al [20] found that CO 2 -enriched produced gas (60-40 mol% CO 2 -CH 4 ) and CO 2 -enriched flue gas (60-40 mol% CO 2 -N 2 ) display ''high oil recovery performance'' and would be efficient choices for gas flooding projects in the Bakken. Two cases were run, each consisting of a 4-cycle Huff-and-Puff treatment.…”
Section: Composition Of the Injection Gasmentioning
confidence: 99%
“…The formation, deposited during Late Devonian and Early Mississipian periods, is overlain by the Lodgepole Formation, an aquifer, and overlays the Torquay Formation (Kreis and Costa, 2005). The Bakken Formation is composed of three members; upper and lower organic-rich black shales, and a middle siltstone to sandstone member (Wang et al, 2010). The reservoir has an initial pressure of 2600 psi and temperature of 156°F (CPE, 2015).…”
Section: Field Study -Viewfield Bakken Oilfieldmentioning
confidence: 99%
“…This makes CO 2 the best candidate for improving the tight oil recovery . Several studies report that it can achieve an incremental oil recovery in the range of 5%‐20% in the Bakken and Eagle ford reservoirs using the huff‐n‐puff gas process . However, some studies also indicate that CO 2 injection does have several drawbacks, including the rapid decline of oil production.…”
Section: Introductionmentioning
confidence: 99%
“…2,[15][16][17][18] Several studies report that it can achieve an incremental oil recovery in the range of 5%-20% in the Bakken and Eagle ford reservoirs using the huff-n-puff gas process. [19][20][21][22][23] However, some studies also indicate that CO 2 injection does have several drawbacks, 24,25 including the rapid decline of oil production. Some have reported that the reservoir pressure during production cycle sharply drops after the first cycle with linear depletion to the minimum pressure.…”
Section: Introductionmentioning
confidence: 99%